2006
DOI: 10.1128/jvi.80.5.2369-2379.2006
|View full text |Cite
|
Sign up to set email alerts
|

Selective Lymphocyte Depletion during the Early Stage of the Immune Response to Foot-and-Mouth Disease Virus Infection in Swine

Abstract: Foot-and-mouth disease virus (FMDV) is the causative agent of a highly contagious vesicular disease of cloven-hoofed animals. In the present study we use FMDV serotype C infection of swine to determine, by analytical techniques, the direct ex vivo visualization of virus-infected immune cells during the first 17 days of infection. We report, for the first time, that FMDV C-S8c1 can infect T and B cells at short periods of time postinoculation, corresponding with the peak of the viremia. There is a significant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 23 publications
8
58
0
Order By: Relevance
“…This is in agreement with the recent findings of experimental studies in pigs, mice and guinea pigs (Bautista et al 2003;Diaz-San Segundo et al 2006;Bartels et al 1994). However, studies on naturally infected animals indicated lymphocytosis and also unaltered leucocyte levels (Mohapatra et al 2005;Gokce et al 2004;Elitok et al 2005).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is in agreement with the recent findings of experimental studies in pigs, mice and guinea pigs (Bautista et al 2003;Diaz-San Segundo et al 2006;Bartels et al 1994). However, studies on naturally infected animals indicated lymphocytosis and also unaltered leucocyte levels (Mohapatra et al 2005;Gokce et al 2004;Elitok et al 2005).…”
Section: Discussionsupporting
confidence: 88%
“…However, studies on naturally infected animals indicated lymphocytosis and also unaltered leucocyte levels (Mohapatra et al 2005;Gokce et al 2004;Elitok et al 2005). Earlier studies have associated the lymphopenia in FMDV infected animals with impaired function of residual T-cells with a transient immunosuppression (Bautista et al 2003;Diaz-San Segundo et al 2006;Ostrowski et al 2005;Parida et al 2006). This facilitates viral pathogenesis including systemic spread and viral shedding into environment to enable its transmission.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A dynamic balance exists between pro-and antiinflammatory components (57) that could be disrupted upon viral infection. Previous studies have shown that during acute FMDV infection in swine, the virus induces an immunosuppressive stage, characterized by T cell unresponsiveness and transient lymphopenia affecting all T cell subsets and correlating with the appearance of viremia (3,26). One possible mechanism by which the virus induces immunosuppression might be related to the production of IL-10 (25), an immunosuppressive cytokine that plays an important stimulatory role in the function of B lymphocytes and the production of antibodies by B1 lymphocytes (2).…”
mentioning
confidence: 99%